Proceedings of Civil Engineering Colloquium 2020 / Dr. Anas Ibrahim ... [et al.]. - Ibrahim, Dr. Anas; Abd Ghani, Dr. Kay Dora; Md Nor, Dr. Noorsuhada; Ng, Dr. Kok Shien; Ismail, Dr. Ruqayyah; Tey, Dr. Li Sian; Idrus, Juliana; Md Hassan, Ahmad Syauqi (2020)
A study on the distribution of throughfall in relation to canopy cover was carried out in a Taman Tunku urban forest in Seberang Perai, Peninsular Malaysia. A plot of 12 m x 12 m was established to measure the distribution of gross rainfall, Pg and throughfall, Tf and to identify the correlation between throughfall and canopy cover in urban forest. Roving methods were used in this study to measure the spatial distribution of throughfall. Nine simple rainfall collectors with diameter of 22 cm were located at sub-grid within the plot and moved to other sub-grid after each rainfall event. One identical type of collector was located at open space within the study area to collect gross rainfall. This study was conducted during the month of March and April 2015 with 31 rainfall events. Hemispherical photography (HP) method using fisheye lens was utilized to capture canopy cover image and analysed using Gap Light Analyzer (GLA) software. The relationship between throughfall and gross rainfall for man-made urban forest shows a strong correlation with r2 values of 0.893. The range of throughfall distribution for this study is 17.4% to 33.3% of gross rainfall while the range of the canopy cover for this study is 53% to 70%. Pearson correlation coefficient was used to analyse the relationship between canopy covers and variation of throughfall. At different intensity of rainfall, the throughfall rate was significantly decreased with the increasing of percentage of canopy cover over the plot (n = - 0.717, p = 0.014 under moderate storm). Hence, the canopy cover was found to be influential in predicting throughfall distribution in urban forest.